Original article Spatial patterns of β-amyloid (Aβ) deposits in familial and sporadic Alzheimer’s disease - A. Armstrong, Richard (Folia Neuropathologica, 2011)
The spatial patterns of the diffuse, primitive, and classic β -amyloid (Aβ) deposits were compared in cortical regions in early-onset familial Alzheimer’s disease (EO-FAD) linked to mutations of the amyloid precursor protein APP) or presenilin 1 (PSEN1) genes, late-onset familial AD (LO-FAD), and sporadic AD (SAD). The objective was to determine whether genetic factors influenced the spatial patterns of the A β deposits. A β deposits were distributed either in clusters which were regularly distributed parallel to the pia mater or in larger, non-regularly distributed clusters. There were no significant differences in spatial pattern of the diffuse deposits between patient groups but mean cluster size of the diffuse deposits was larger in FAD compared with SAD. Primitive A β deposits were more frequently distributed in regular clusters and less frequently distributed in large clusters in FAD compared with SAD. Classic A β deposits were more frequently distributed in regularly spaced clusters and less frequently distributed in large clusters in LO-FAD compared with EO-FAD. There were no significant differences in the spatial patterns or cluster sizes of A β deposits in cases classified according to apolipoprotein E (APOE) genotype. These results suggest (1) greater deposition of A β in the form of clusters of diffuse deposits in FAD, (2) a greater proportion of diffuse deposits may be converted to primitive deposits in SAD, (3) classic deposits are more widely distributed in EO-FAD, and (4) the presence of APOE allele ε4 has little effect on the spatial patterns of A β deposits.